Fulfilling Communal Rights through the Implementation of the Second Principle of Pancasila towards the Regulation on Agrarian Reform - Kartika Winkar Setya; Abdul Aziz Nasihuddin; Izawati Wook (Faculty of Sharia Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Indexed by Scopus